Preboard 1 Answer Key
Preboard 1 Answer Key
Preboard 1 Answer Key
Maths
General Instructions: -
This question paper contains five sections A, B, C D and E. Each section is compulsory. However, there are internal choices in some questions.
Section A has 18 MCQ’s and 2 Assertion – Reason based questions of 1 mark each.
Section B has 5 Very Short Answer (VSA) type questions of 2 marks each.
Section C has 6 Short Answer (SA) type questions of 3 marks each.
Section D has 3 source based/ case passage based/ integrated units of assessment (4 marks each) with sub parts.
Section E has 4 Long Answer (LA) type questions of 5 marks each.
Total Marks : 80
SECTION A 18 x 1 = 18
1) (a) ± 3
2) (a) 12m and 18m
3) (b) a = 0 and b can take any real value
4) (a) 6
5) (c) 1
6) (a) (0,-1)
7) (b) Square
8) (c) 7.5
9) (b) 245
10) (d) None of these
11) (d) -2, 1
12) (d) 2
c
13) (b) a
14) (c) 60
15) (c) 3 km/h
16) (d) 2x+ y=3,-4x+2y=10
17) (c) 90°
18) (b) 10 cm
ASSERTION-REASON BASED QUESTIONS 2x1=2
22) Let P(x, y) be equidistant from the points A(7, 1) and B(3, 5). We are given that AP = BP. So, AP2 = BP2
i.e., (x – 7)2 + (y – 1)2 = (x – 3)2 + (y – 5)2
i.e., x2 – 14x + 49 + y2 – 2y + 1 = x2 – 6x + 9 + y2 – 10y + 25
i.e., x – y = 2
which is the required relation.
23) If the number 4n , for any n, were to end with the digit zero, then it would be divisible by 5. That is, the prime
factorisation of 4n would contain the prime 5. This is not possible because 4n = (2)2n ; so the only prime in the
factorisation of 4n is 2. So, the uniqueness of the Fundamental Theorem of Arithmetic guarantees that there are no
other primes in the factorisation of 4n . So, there is no natural number n for which 4n ends with the digit zero.
You have already learnt how to find the HCF and LCM of two positive integers using the Fundamental Theorem of
Arithmetic in earlier classes, without realising it. This method is also called the prime factorisation method. Let us
recall this method through an example.
24) a)
Given equation (x-3)(2x+1)=x(x+5)
2x2 + x - 6x - 3 = x2 + 5x
⇒ 2x
2 + x - 6x - 3 - x2 - 5x = 0
⇒ x
2 - 10x - 3 = 0 has its highest power 2
b) 2 1
2x − x + = 0
8
2
16x −8x+1
= 0
8
16x2-4x-4x+1=0
4x(4x+1)-1(4x-1)=0
(4x-1)(4x-1)=0
4x-1=0 or 4x-1=0
1 1
x = or x =
4 4
1 1
Hence the roots are, 4
,
4
25) a)
0, √5
If a = 1, b = 0, c = √5
Therefore, the quadratic polynomial is x
2
+ √5
(OR)
If a = 1, b = -1, and c = 1
Therefore, the quadratic polynomial is x2 – x +1.
SECTION C 6 x 3 = 18
26) 6 +√2
if possible let a = 6 +√2 be a rational number.
Squaring a2 = (6 + √2)2
a2 =38 + 12√2
2
a −38
√2 = − (1)
12
2
a −38
Since a is a rational number the expression 12
is also rational number.
⇒ √2 is a rational number.
This is a contradiction. Hence, 6 +√2 is irrational.
Hence proved.
27) Let p(t) = t2 - 15 = t2 - −− 2
(√15 )
−− −−
= (t - √15 )(t + √15 ) [∵ a2 - b2 = (a - b) (a + b)]
To find zeroes, put p(t) = 0
−− −−
⇒ (t − √15 )(t + √15 ) = 0
−− −− −− −−
⇒ t − √15 = 0 or t + √15 = 0 ⇒ t = √15 or t = -√15
−− −−
Hence, zeroes of the given polynomial are -√15 and √15 .
Verification
−− −−
Hence, sum of zeroes = -√15 + √15 = 0 = -(0/1)
C oef f icient of t
= − 2
C oef f icient of t
−− −− −15
and product of zeroes = -√15 × √15 = -15 = 1
C onstant term
=
2
C oef f icient of t
So, the relationship between the zeroes and its coefficients is verified.
28) Given, △ABE ≅ △AC D
⇒ AB = AC and AE = AD [by CPCT]
AB
⇒ = 1
AC
AD
and = 1
AE
AB AD
⇒ = .... (i)
AC AE
b) Let the first term and the common difference of the given AP be a and d, respectively.
According to the question,
Third term + Seventh term = 6
⇒ (a + 2d) + (a + 6d) = 6
⇒ a + 4d = 3 ....(i)
⇒ a + 2 = 3
⇒ a = 3 − 2 ⇒ a = 1
15 19
= 8 (2 + ) = 8( ) = 76
2 2
1
When, d = - 2 , then from Eq. (i), we get
1
a + 4 (− ) = 3 ⇒ a − 2 = 3 ⇒ a = 5
2
1 15 5
= 8 [2(5) + 15 (− )] = 8 (10 − ) = 8( ) = 20
2 2 2
b) 2x − 2y − 2 = 0
4x − 4y − 5 = 0
a1 2 1 b1 −2 1 c1 2
= = , = = , =
a2 4 2 b2 −4 2 c2 5
a1 b1 c1
Since = ≠
a2 b2 c2
Therefore, these linear equations are parallel to each other and thus have no possible solution. Hence, the pair
of linear equations is inconsistent
SECTION D 3 x 4 = 12
32) (i) (b): Let two consecutive integers be x, x + 1.
Given, x2 + (x + 1)2 = 650
2
⇒ 2x + 2x + 1 − 650 = 0
2
⇒ 2x + 2x − 649 = 0
⇒ 10(15 − x + x) = 3x(15 − x)
2 2
⇒ 50 = 15x − x ⇒ x − 15x + 50 = 0
−−−−−−−−−−−−−−− −−
(iii) (c) : AB 2 2
= √(7 − 2) + (7 − 8) = √26 units
−−−−− − −−
2 2
OA = √2 + 8 = 2√17 units
−−−−−−−−−−−−−−−
2 2
BC = √(7 − 5) + (7 − 3) = 2√5 units
∴ BC is the least.
(iv) (c)
5+7 3+7
(v) (b): Coordinates of D = (
2
,
2
) = (6, 5)
(ii) (a): The zeroes of the polynomial are the points where its graph intersect the x-axis.
(iii) (d)
(iv) (d)
8√3
(v) (c): Product of zeroes = = 8.
√3
SECTION E 4 x 5 = 20
[∵ −5x(2) = −10
and − 5 + 2 = −3]
⇒ x(x − 5) + 2(x − 5) = 0
⇒ x − 5 = 0 ⇒ x = 5
⇒ x + 2 = 0 ⇒ x = −2
36) From the given figure,the coordinates of points A, B, C and D are (3,4), (6, 7), (9, 4) and (6, 1),respectively.
−−−−−−−−−−−−−−−
Now, AB = √(6 − 3)
2
+ (7 − 4)
2
−−−−−−−−−−−−−−−−−−
2 2
[∵ distance = √ (x 2 − x 1 ) + (y2 − y1 ) ]
−−−−−− −−−− −−
2 2
= √3 + 3 = √9 + 9 = √18 = 3√2 units
−−−−−−−−−−−−−−−
2 2
BC = √(9 − 6) + (4 − 7)
−−−−−−−−−
2 2 −−−− −−
= √3 + (−3) = √9 + 9 = √18 = 3√2 units
−−−−−−−−−−−−−−−
2 2
C D = √(6 − 9) + (1 − 4)
−−−−−−−−−−−
2 2 −−−− −−
= √(−3) + (−3) = √9 + 9 = √18 = 3√2 units
−−−−−−−−−−−−−−−
2 2
DA = √(3 − 6) + (4 − 1)
−−−−−−−−−
2 2 −−−− −−
= √(−3) + 3 = √9 + 9 = √18 = 3√2 units
−−−−−−−−−−−−−−−
2 2
AC = √(9 − 3) + (4 − 4)
−−−−− −−
= √36 + 0 = √36 = 6 units
−−−−−−−−−−−−−−−
−−−−− −−
and BD = √(6 − 6)
2
+ (1 − 7)
2
= √0 + 36 = √36 = 6 units
Here, all the four sides (AB, BC, CD, DA) are equal and diagonals (AC, BD) are equal.
Hence, ABCD is a square. So, Champa is correct.
37) a)
Given AP is 121, 117, 113,...
Here, first term, a = 121
and common difference, d = 117 - 121 = -4
Let,the nth term of this AP be the first negative term.Then,
an < 0
⇒ x2 = 1225
⇒ x = ±35
Since, x is a counting number.
∴ Taking positive sign, we get x = 35.
38) a)
Given, a pair of linear equations is :
0.2x + 0.3y = 1.3 .....(i)
and 0.4 x + 0.5y= 2.3 ....(ii)
Multiply both sides of Eq. (i) and Eq. (ii) by 10, we get
2x + 3y = 13 ....(iii)
and 4x + 5y = 23 ....(iv)
On substituting y from eqn. (iii) in eqn. (ii),
(13−2x)
4 5 23
x + × =
10 10 3 10
5
⇒ 4x + (13 − 2x) = 23
3
⇒ 2x = 69 - 65 = 4
∴ x = 2
i.e., y = 3
Hence, x = 2,y = 3
(OR)
Note: This service is not intended for secure transactions such as banking, social media, email, or purchasing. Use at your own risk. We assume no liability whatsoever for broken pages.
Alternative Proxies: